Giant arachnoid cyst associated with acute subdural haematoma: A case report. Issue 3 (June 2017) - Di Gaeta, Alfredo; Giurazza, Francesco; Guarnieri, Gianluigi; Muto, Mario
Arachnoid cysts are extra-cerebral, intra-arachnoidal cerebrospinal fluid collections – the most frequent congenital developmental intracranial cystic lesions. They are often diagnosed incidentally during imaging exams acquired for different reasons, and are usually asymptomatic. Rare complications are post-traumatic rupture with consequent subdural haematomas. Spontaneous bleeding should be acknowledged as a rare but possible complication of this benign lesion. We report on the case of a patient presenting with a giant arachnoid cyst extending to the left frontal, temporal and parietal lobes associated with acute subdural haematoma without history of trauma.